2022
DOI: 10.1186/s42155-022-00342-x
|View full text |Cite
|
Sign up to set email alerts
|

A modified two-step technique for the retrieval of a chemoport catheter fragment with inaccesible ends

Abstract: Background Migration of central venous catheters is a rare but serious complication. The endovascular approach has been widely used for the retrieval of such fragment, with the two-step technique used for removal of catheter fragments with inaccessible ends. In this case report, we describe a modification of this technique that was used after first attempting the two-step technique unsuccessfully. Case presentation A 42-year-old female with breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Previous reports have shown that the pigtail catheter was effective in removing catheter fragments without accessible ends, leading to the development of the Wire TRUST technique utilizing the pigtail catheter. 8 , 9 A 4‐Fr pigtail catheter (Terumo) must be positioned at the targeted lead using multidirectional fluoroscopic guidance to initiate the Wire TRUST technique. In situations where positioning the catheter is challenging, such as with an enlarged heart, using a steerable introducer might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that the pigtail catheter was effective in removing catheter fragments without accessible ends, leading to the development of the Wire TRUST technique utilizing the pigtail catheter. 8 , 9 A 4‐Fr pigtail catheter (Terumo) must be positioned at the targeted lead using multidirectional fluoroscopic guidance to initiate the Wire TRUST technique. In situations where positioning the catheter is challenging, such as with an enlarged heart, using a steerable introducer might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The Wire TRUST technique is relatively simple and effective for grasping a lead with inaccessible ends. Previous reports have shown that the pigtail catheter was effective in removing catheter fragments without accessible ends, leading to the development of the Wire TRUST technique utilizing the pigtail catheter 8,9 . A 4‐Fr pigtail catheter (Terumo) must be positioned at the targeted lead using multidirectional fluoroscopic guidance to initiate the Wire TRUST technique.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approaches, including venotomy and median sternotomy, are no longer recommended for stuck port retrieval due to their invasive nature. Currently, endovascular retrieval is the preferred procedure, including techniques such as using a guidewire to exert direct force on the catheter by applying a combination of ‘pull-out’ and ‘push-in’ forces along a guidewire, pushing the catheter via a dilator during snaring, utilizing a pigtail catheter with a snare, and endoluminal dilatation with a balloon [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the two-step retrieval procedure and its modified versions all carry the risk of the free end of the dislodged catheter passing into the heart, making it impossible to retrieve the entire catheter [ 8 ]. Furthermore, in techniques that involve squeezing forces, the use of excessive force may lead to further fracture of the dislodged catheter or puncturing of the vessel wall [ 6 ].…”
Section: Introductionmentioning
confidence: 99%